Protection of Shareholders Through Shareholders Agreement (Study: Comparison of Indonesian and Canadian Laws) - Alya, Farah; Wahyuni, Ridha (PALAR (Pakuan Law review), 2026)
Abstract Protection for shareholders is essential in corporate practice to provide legal certainty for shareholders. This study aims to analyze the effectiveness of shareholders agreements as an important instrument for overcoming the limitations of articles of association in order to increase legal certainty for shareholders, as well as to analyze legal comparisons between Indonesia and Canada regarding the regulation of shareholders agreements in order to increase legal certainty for shareholders. The research method used is normative juridical, with a legislative approach and a comparative law approach. The results of the study show that in Indonesia, shareholders agreements are recognized as civil agreements that are binding on the parties as long as they do not conflict with the UUPT and the articles of association. However, in Indonesia, this is not explicitly regulated in the law. In contrast, in Canada, shareholders agreements have obtained special provisions through the Unanimous Shareholders Agreement (USA), which can explicitly limit or take over some of the authority of the board of directors. In Canada, shareholders agreements can be an alternative for dispute resolution. This study recommends harmonizing shareholders agreements with the articles of association and explicit provisions regarding shareholders agreements. Keywords: Shareholder Protection, Shareholders Agreement, Indonesian Law, Canadian Law.